Urban environment and health: a cross-sectional multiregional project based on population health surveys in Spain (DAS-EP project) – study protocol - Andrés Cabrera-León; Antonio Daponte; Marc Saez; Katherine Pérez; María Rueda; Ferran Ballester; Ana Esplugues; Aitana Lertxundi; Laia Font-Ribera; Laura Oliveras; Marina Lacasaña; Marisa Estarlich; et al. (BMJ Open)
Introduction The European Environment Agency estimates that 75% of the European population lives in cities. Despite the many advantages of city life, the risks and challenges to health arising from urbanisation need to be addressed in order to tackle the growing burden of disease and health inequalities in cities. This study, Urban environment and health: a cross-sectional multiregional project based on population health surveys in Spain (DAS-EP project), aims to investigate the complex association between the urban environmental exposures (UrbEEs) and health.Methods and analysis DAS-EP is a Spanish multiregional cross-sectional project that combines population health surveys (PHS) and geographical information systems (GIS) allowing to collect rich individual-level data from 17 000 adult citizens participating in the PHS conducted in the autonomous regions of the Basque Country, Andalusia, and the Valencian Community, and the city of Barcelona in the years 2021–2023. This study focuses on the population living in cities or metropolitan areas with more than 100 000 inhabitants. UrbEEs are described by objective estimates at participants’ home addresses by GIS, and subjective indicators present in PHS. The health outcomes included in the PHS and selected for this study are self-perceived health (general and mental), prevalence of chronic mental disorders, health-related quality of life, consumption of medication for common mental disorders and sleep quality. We aim to further understand the direct and indirect effects between UrbEEs and health, as well as to estimate the impact at the population level, taking respondents’ sociodemographic and socioeconomic characteristics, and lifestyle into consideration.Ethics and dissemination The study was approved by the regional Research Ethics Committee of the Basque Country (Ethics Committee for Research Involving Medicinal Products in the Basque Country; PI2022138), Andalusia (Biomedical Research Ethics Committee of the Province of Granada; 2078-N-22), Barcelona (CEIC-PSMar; 2022/10667) and the Valencian Community (Ethics Committee for Clinical Research of the Directorate General of Public Health and Center for Advanced Research in Public Health; 20221125/04). The results will be communicated to the general population, health professionals, and institutions through conferences, reports and scientific articles.